DIAGNOSTICAL EXPLORATION ON THE DISEASE PRESENTED AS ACUTE CORONARY SYNDROME, AT THE AGE OF GENETICS. CLINICAL CASE - N. S. Krylova (Российский кардиологический журнал, 2016)
An unusual case presented, of the disease onset as acute coronary syndrome in 65-year old woman. Based on ECG data, laboratory tests, echocardiography, coronary arteriography and Gadolinium MRI of the heart, coronary heart disease was ruled out, and hypertrophic cardiomyopathy (HCM) suspected. The specifics of current case is absence of the classical signs of HCM on echocardiography: LV hypertrophy was not prominent and was symmetric. Apical HCM was suspected due to specific ECG changes with the giant negative T-waves in left precordial leads, and specifics of delayed deposition of contrast media in MRI. Genetics of the patient’s saliva specimen revealed mutation Asp75Asn in myosin binding protein C, which has been previously described just in 7 HCM families. Restricted number of patients with this mutation makes it not possible to be sure of the grade of severity. Dynamic follow-up is recommended of the patient with the aim to prevent disease progression and its complications prevention.